Implementasi Manajemen Pendidikan Karakter dalam Upaya Meningkatkan Karakter Siswa Perspektif Islam - Muhammad Naufal Sauqy; Hinggil Permana (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The purpose of this study is to analyze the management of character education in schools from an Islamic perspective. The research method used is a qualitative method with a library research approach. The results of this study indicate that character education has a higher meaning than moral education, therefore character education not only teaches right and wrong, but at the same time instills habits (habituation) about good so that students become aware, able to feel, and want to do what is good. In the Islamic view, that character is called morals. Components of moral education or personality include: knowledge, attitudes, and behavior and are identical with the teachings of Islam itself which are sourced from the Qur'an and al-Hadith. Thus, it can be stated that the Islamic perspective of character education is a system of behavior that is required in the Islamic religion as stipulated through the Qur'an and al-Hadith Rasulullah saw. Implementation of character education in Islam according to the hadith of the Messenger of Allah, can be classified in 6 stages, namely: 1) Tawhid (starting from 0-2 years); 2) Adab (5-6 years); 3) Self-responsibility (7-8 years); 4) Caring-Caring (9-10 years); 5) Independence (11-12 years), and 6) Community (13 years and above).